The Revolutionary Tendency of Gibran Khalil Gibran: A Descriptive Analytical Study - Hüseyin Esved; Mahmoud Bakdash (Şarkiyat Mecmuası)
This study deals with the revolutionary tendency of the Lebanese writer, poet, and artist Khalil Gibran according to the descriptive and analytical approaches, as it monitors the most important factors that contributed to the formation of Gibran’s methodology of revolutionary thought. These factors are represented in his upbringing, formation, environment in which he lived, the harsh conditions of diasporic exile, and the bitter reality of his country, as well as the influence from the ideas of the German philosopher Nietzsche. The study also focuses on the most important revolutionary issues that he discussed in his books, revealing their diversity through his revolt against religious tyranny and improper practices of the clergy as well as his revolt against feudal and influential people such as corrupt rulers and judges. His revolution also involved social grievances and certain corrupt traditions and customs. The article goes on to talk about Gibran’s revolution against himself and then concludes by presenting several of the following results. Gibran’s revolutionary tendency was not a mutation; instead, its signs had appeared since his childhood and the circumstances he experienced contributed to their development, with Gibran’s favorite tool for raising issues being the story. The study recommends that researchers study the literature on stories and method of story employment Gibran used. The study also recommends examining the principles and values that Gibran appealed to with regard to the issues he addressed and revolted against.